The Role of Income and Gender Inequalities in the Spread of the HIV/AIDS Epidemic: Evidence from Sub-Saharan Africa - (:unkn) unknown (My University, 2008)
Throughout African continent, HIV/AIDS epidemic has became a major cause of death and poverty. Nonetheless, the relation between poverty and HIV/AIDS epidemic is not as straightforward as it might first appear. Indeed, if at the international level the most affected regions are the poorest, in Sub-Saharan Africa however, the most affected countries also happen to be the richest. Meanwhile, these countries are also those with the least egalitarian income distributions in the world. Moreover, the distribution of the epidemic across both sexes differs according to regions, with Sub-Saharan Africa being the most gender-affected region: more than half of infected people there are women. Our focus in this dissertation is to assess the importance of income and gender inequalities as determinants of the spread of HIV/AIDS pandemic in Sub-Saharan Africa. Using a panel data of 42 African countries from the period 1997-2005, we examine the link between income and gender inequalities on the one hand and HIV/AIDS epidemic on the other hand by introducing these variables among the traditional determinants of the epidemic. Our results suggest that there is indeed a link between income inequality and HIV/AIDS epidemic. Moreover, the correlation remains even after we control for poverty and when we perform a dynamic analysis of the epidemic. Furthermore, women's education and economic independence appear to be critical determinants of the pandemic. Specifically, our results indicate that the component of gender inequality which drives the epidemic among young population (15-24) is gender inequality in income and participation to economic life, while it is gender inequality in education which fuels the epidemic among adult population (15-49).
Keywords: African Research